Thrombotic microangiopathy in children - Palma, Lilian Monteiro P.; Vaisbich-Guimarães, Maria Helena; Sridharan, Meera; Tran, Cheryl L.; Sethi, Sanjeev (Springer Nature, 2022)
The syndrome of thrombotic microangiopathy (TMA) is a clinical-pathological entity characterized by microangiopathic hemolytic anemia, thrombocytopenia, and end organ involvement. It comprises a spectrum of underlying etiologies that may differ in children and adults. In children, apart from ruling out shigatoxin-associated hemolytic uremic syndrome (HUS) and other infection-associated TMA like Streptococcus pneumoniae-HUS, rare inherited causes including complement-associated HUS, cobalamin defects, and mutations in diacylglycerol kinase epsilon gene must be investigated. TMA should also be considered in the setting of solid organ or hematopoietic stem cell transplantation. In this review, acquired and inherited causes of TMA are described with a focus on particularities of the main causes of TMA in children. A pragmatic approach that may help the clinician tailor evaluation and management is provided. The described approach will allow for early initiation of treatment while waiting for the definitive diagnosis of the underlying TMA.
Keywords: Complement; DGKe; Hemolytic uremic syndrome; Hypertension; Infection; Thrombotic microangiopathy; Transplant